2007
DOI: 10.1007/s10509-007-9391-1
|View full text |Cite
|
Sign up to set email alerts
|

A photometric study of the Algol-type binary AB Cas

Abstract: We present new photoelectric observations of the eclipsing binary system AB Cas, together with an analysis of the light curves. Using the available times of light minimum reported in the literature together with our own minima, period changes are monitored, and the possible thirdbody parameters are obtained. The absolute properties of the system and the delta-Scuti behavior of the primary are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…The above authors concluded that the period of this system undergoes both secular changes due to mass transfer (d P /d t = 0.03 s yr −1 ) and cyclic period modulations due to the presence of a third body with a period of P 3 = 40.3 yr and a mass of M 3 ≥ 0.31 M ⊙ . Later, a similar study was carried out by Abedi & Riazi (2007). They also interpreted the O−C curve as a secular period change superimposed on cyclic variations in P , and found the rate of period change to be d P /d t = 0.05 s yr −1 and the parameters of the third body to be P 3 = 25.6 yr and M 3 ≥ 0.21 M ⊙ .…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…The above authors concluded that the period of this system undergoes both secular changes due to mass transfer (d P /d t = 0.03 s yr −1 ) and cyclic period modulations due to the presence of a third body with a period of P 3 = 40.3 yr and a mass of M 3 ≥ 0.31 M ⊙ . Later, a similar study was carried out by Abedi & Riazi (2007). They also interpreted the O−C curve as a secular period change superimposed on cyclic variations in P , and found the rate of period change to be d P /d t = 0.05 s yr −1 and the parameters of the third body to be P 3 = 25.6 yr and M 3 ≥ 0.21 M ⊙ .…”
Section: Introductionmentioning
confidence: 74%
“…The derivative of JD with respect to E yields the period at any arbitrary time‐instant: We now differentiate this formula with respect to time to obtain because , . We then substitute formula (6) for into to obtain (with the approximation P ≈ P 0 ) The parameters of the star AB Cas are equal to: M 1 = 1.875 M ⊙ , M 2 = 0.375 M ⊙ (Abedi & Riazi 2007), q = 0.20, 2 A = 1.374 × 10 −9 d, P = 1.366 88 d. We substitute these quantities into to obtain M ⊙ yr −1 .…”
Section: Orbital Period Changes In Ab Casmentioning
confidence: 99%
See 3 more Smart Citations